CAPITULO III: Parodia y creación. - Urbina, Eduardo (Principios y Fines de Quijote, 1990)
The book "Principios y Fines de Quijote," written by Eduardo Urbina and published by Scripta Humanistica in 1990, is presented. The author explores the narrative uses of irony, parody and the grotesque in Spanish author Miguel de Cervantes' book "Don Quijote" and its significance in relation to Medieval literary genres.